CROSS-CULTURAL COMMUNICATION: STRATEGIC AND PERSUASIVE DISCOURSE IN ITALIAN AND UZBEK LINGUOCULTURES - Gulamova Malika Yakubovna (Next Scientists Conferences, 2025)
This article explores the interplay between communicative strategies and persuasive discourse within Italian and Uzbek linguocultures, highlighting their distinct cultural and linguistic norms. Drawing on the principles of pragmatics, discourse analysis, and intercultural communication theory, the study examines how speakers in each culture use language to influence, request, and negotiate meaning within various social contexts. The paper focuses on directness vs. indirectness, politeness strategies, and culturally embedded values such as collectivism in Uzbek society and individual expressiveness in Italian discourse. Through a comparative lens, specific speech acts—such as requests, suggestions, and commands—are analyzed to identify recurrent tactics and their sociocultural motivations. The findings reveal that while both cultures aim to achieve persuasive goals, they rely on fundamentally different linguistic forms and pragmatic cues shaped by their respective communicative traditions. This research contributes to a deeper understanding of intercultural pragmatics and supports the development of more culturally responsive approaches in translation, diplomacy, and language education.